Evaluation of the Allplex™ GI-Helminth(I) Assay, the first marketed multiplex PCR for helminth diagnosis - Autier Brice; Gangneux Jean-Pierre; Robert-Gangneux Florence (Parasite, 2021)
Molecular biology has been gaining more importance in parasitology. Recently, a commercial multiplex PCR assay detecting helminths was marketed: the Allplex™ GI-Helminth(I) Assay. It targets Ancylostoma spp., Ascaris spp., Enterobius vermicularis, Hymenolepis spp., Necator americanus, Strongyloides spp., Taenia spp. and Trichuris trichiura, but also the two most common microsporidia genera in human health, i.e. Enterocytozoon spp. and Encephalitozoon spp. This study aimed to evaluate and compare the Allplex™ GI-Helminth(I) Assay to classical diagnostic methods, based on a cohort of 110 stool samples positive for helminths (microscopy) or for microsporidia (PCR). Samples were stored at −80 °C until analysis by the Allplex™ GI-Helminth(I) Assay. False-negatives were re-tested with bead-beating pretreatment. Without mechanical lysis, concordance and agreement between microscopy and Allplex™ GI-Helminth(I) Assay ranged from 91% to 100% and from 0.15 to 1.00, respectively depending on the target. Concordance was perfect for Taenia spp. (n = 5) and microsporidia (n = 10). False-negative results were observed in 54% (6/13), 34% (4/11) and 20% (7/35) of cases, for hookworms, E. vermicularis and Strongyloides spp. detection, respectively. For these targets, pretreatment improved the results, but only slightly. Trichuris trichiura detection was critically low without pretreatment, as only 9% (1/11) of the samples were positive, but detection reached 91% (10/11) with bead-beating pretreatment. Mechanical lysis was also needed for Ascaris spp. and Hymenolepis spp. to reduce false-negative results from 1/8 to 1/21, respectively, to none for both. Overall, with an optimized extraction process, the Allplex™ GI-Helminth(I) Assay allows the detection of numerous parasites with roughly equivalent performance to that of microscopy, except for hookworms.